Leadership Behavior Impact on Safety Culture in Jeddah Eye Hospital - Almuntasheri, Amal Ali; Almandeel, Seita Mandeel (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to investigate the relationship between leadership behaviour, safety culture, and safety performance in the healthcare industry as well as review recent articles on patient safety culture. to explore leadership practices within employee relationship, tasks done, openness of communication, organizational structure and teamwork and response to an error. Besides, the study aims to explore the degree of awareness of the safety culture among workers at Jeddah Eye Hospital and explore the leadership role in the Safety Culture at Jeddah Eye Hospital. The study followed the cross- sectional approach in which 350 questionnaires were delivered to hospital employees, with 195 valid responses; 55.7% valid response rate. Confirmatory factor analysis (CFA) was used to examine the factor structure and see if the composite reliability was significant with a factor loading of >0.5, resulting in an acceptable model fit. according to the results of a one- way ANOVA analysis, physicians have much more unfavourable patient safety culture perceptions and safety performance perceptions than non- physicians. The results of the route analysis demonstrate that leadership conduct has an impact on safety culture and performance in the healthcare industry. Contingency leadership and a favourable patient safety organization culture influenced and improved safety performance. The study also revealed that a well- managed system that combines leadership considerations, hospital staff training courses, and a reliable safety reporting system can improve safety performance.